Viable Compositional Analysis of an Eleven Species Oral Polymicrobial Biofilm - Sherry, Leighann; Lappin, Gillian; O'Donnell, Lindsay E.; Millhouse, Emma; Millington, Owain R.; Bradshaw, David J.; Axe, Alyson S.; Williams, Craig; Nile, Christopher J.; Ramage, Gordon (Frontiers in Microbiology, 2016)
Purpose Polymicrobial biofilms are abundant in clinical disease, particularly within the oral cavity. Creating complex biofilm models that recapitulate the polymicrobiality of oral disease are important in the development of new chemotherapeutic agents. In order to do this accurately we require the ability to undertake compositional analysis, in addition to determine individual cell viability, which is difficult using conventional microbiology. The aim of this study was to develop a defined multispecies denture biofilm model in vitro, and to assess viable compositional analysis following defined oral hygiene regimens. Methods An in vitro multispecies denture biofilm containing various oral commensal and pathogenic bacteria and yeast was created on poly (methyl methacrylate) (PMMA). Denture hygiene regimens tested against the biofilm model included brushing only, denture cleansing only and combinational brushing and denture cleansing. Biofilm composition and viability were assessed by culture (CFU) and molecular (qPCR) methodologies. Scanning electron microscopy and confocal laser scanning microscopy were also employed to visualise changes in denture biofilms following treatment. Results Combinational treatment of brushing and denture cleansing had the greatest impact on multispecies denture biofilms, reducing the number of live cells by more than 2 logs, and altering the overall composition in favour of streptococci. This was even more evident during the sequential testing, whereby daily sequential treatment reduced the total and live number of bacteria and yeast more than those treated intermittently. Bacteria and yeast remaining following treatment tended to aggregate in the pores of the PMMA, proving more difficult to fully eradicate the biofilm. Conclusions Overall, we have developed a method to enable viable compositional analysis of an 11 species denture biofilm to evaluate various denture cleansing regimens. We were able to demonstrate viable cell reduction and changes in population dynamics. Specifically, it was demonstrated that daily combinational treatment of brushing and cleansing proved to be the most advantageous denture hygiene regimen, however, residual organisms remained within the pores of PMMA surface which could act as a reservoir for further biofilm regrowth. We have identified an industry need for denture cleansing agents with the capacity to penetrate these pores and disaggregate these complex biofilm consortia.